Discrimination – substitute for competence and indicator of poor administration (governance) - Vasile Burtea (Sfera Politicii, 2014)
The present study attempts to define the concept of discrimination, in order to highlight several manifestation forms, this endeavour being absolutely necessary with relation to its analysis, making possible the moral and the judicial sanction exerted by society. Keeping in mind that discrimination is venom to society, as well as to the connections between its members, the demonstation of the discriminatory deed requires credible and credible instruments and means.